Noninvasive cerebral oximetry during carotid endarterectomy: application and results - Kontrimavičiūtė, Eglė; Kuzminskaitė, Vilma; Šipylaitė, Jūratė (Acta medica Lituanica, 2015)
Background. Cerebral monitoring during carotid endarterectomy allows to detect brain hypoperfusion following carotid clamping and hyperperfusion after restoring the blood flow. Immediate corrections of these changes have the potential in reducing adverse neurologic outcomes. In this study we share our experience using cerebral oximetry in carotid endarterectomy surgery, as well as finding a connection between comorbidities and baseline cerebral oxygenation values. Materials and methods. A non-randomised perspective study was performed at Vilnius University Hospital Santariškių Clinics. During 2012–2013 all consecutive elective patients undergoing carotid surgery were enrolled in the study. Results. No difference was found in the baseline values on the operative and control sides (71.15% vs 76.76%, p = 0.15). After carotid clamping regional brain saturation decreased by 4.34% of the baseline on the operative side. During the clamping cerebral oxygenation was lower on the operative side (68.06% vs 77.32%, p = 0.03). Following carotid declamping the difference between operative and control side oxygenation diminished (73.57% vs 79.30%, p = 0.16). Neither diabetes nor peripheral atherosclerosis had influence on baseline cerebral oxygen saturation values. There was a tendency towards the lower cerebral oxygenation baseline for smokers (70.12% vs 76.54%, p = 0.103). Conclusions. Cerebral oximetry is a valuable method of cerebral monitoring reflecting changes in brain perfusion during carotid endarterectomy. Certain comorbidities might have a role in affecting baseline oximetry values.
Keywords: baseline; cerebral oximetry; comorbidities; endarterectomy